AASB 138: catalyst for managerial decisions reducing R&D spending?. Issue 1 (4th July 2016) - Steenkamp, Natasja; Steenkamp, Shaun
Abstract : Purpose: This paper aims to investigate if the more stringent requirements of AASB 138, effective 1 January 2005, regarding capitalising research and development (R&D) spending could have been a catalyst for changes in managerial decisions that consequently resulted in reduced R&D spending in Australian companies. Design/methodology/approach: Financial data of 31 Australian listed firms for financial years from 2001 to 2010 were used. Companies were classified as either capitalisers or non-capitalisers. A regression model was used to ascertain whether managers reduced R&D spending to manage earnings to attain short-term goals. Also, the research intensity ratios were calculated to determine trends in R&D spending of the two groups. Findings: The pursuit of choosing short-term earnings targets to the detriment of long-term returns is referred to as short-termism. This study found a marked increase in the significance of short-termism in explaining changes in R&D of capitalisers before 2005. Furthermore, the median research intensity ratio of capitalisers declined almost three times that of non-capitalisers after the introduction of AASB 138. These findings suggest that AASB 138 could have been a catalyst for changes in managerial decisions in pursuit of short-termism, resulting in reduced R&D spending as a means to manage earnings. Originality/value: This study is useful to standard setters and board of directors as it alerts them about the potential adverse effect AASB 138 might have on the survivability and competitiveness of Australian companies and hence the Australian economy.